Lipoprotein(a) in endurance athletes, power athletes, and sedentary controls - Halle, M.; Berg, A.; von Stein, T.; Baumstark, M. W.; Konig, D.; Keul, J. (Medicine & Science in Sports & Exercise, 1996)
Elevated concentrations of lipoprotein(a) [Lp(a)] have been shown to be an independent risk factor for atherosclerotic disease. Physical activity and physical fitness have been shown to improve lipoprotein metabolism and reduce the risk of coronary artery disease. Studies on the influence of physical activity and physical fitness on Lp(a) levels including a large number of endurance as well as power athletes have not been performed before. Therefore, we determined parameters of physical fitness (maximal oxygen consumption), physical activity, and lipoproteins in 105 endurance athletes, 57 power athletes, and 87 sedentary young men. As expected, we found that endurance athletes with a good physical fitness had significantly higher concentrations of high-density lipoprotein cholesterol than power athletes and sedentary controls. Regarding mean Lp(a) levels (rocket immunoelectrophoresis), however, there were no significant differences between endurance athletes, power athletes, and sedentary controls. Even when including only those with Lp(a) values > 10 mg.dl-1, no differences were observed between the groups. These findings indicate that intensive training over years and good aerobic fitness improve the ratio of low-density lipoprotein to high-density lipoprotein cholesterol but have no or only minor effects on Lp(a) concentrations.